2008
DOI: 10.1080/10550880802122646
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapeutic Benefits of Opioid Agonist Therapy

Abstract: Opioids have been used for centuries to treat a variety of psychiatric conditions with much success. The so-called "opium cure" lost popularity in the early 1950s with the development of non-addictive tricyclic antidepressants and monoamine oxidase inhibitors. Nonetheless, recent literature supports the potent role of methadone, buprenorphine, tramadol, morphine, and other opioids as effective, durable, and rapid therapeutic agents for anxiety and depression. This article reviews the medical literature on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(84 citation statements)
references
References 66 publications
0
81
0
2
Order By: Relevance
“…However, most publications seem to agree on the general anxiolytic status of morphine. In fact, morphine has already been shown to decrease fear-and anxiety-related behaviors in rhesus monkeys [59] and in humans [60]. Furthermore, injection of morphine in healthy rats either has no effect [26] or induces anxiolytic effects [61,62] when tested in the EPM.…”
Section: Discussionmentioning
confidence: 99%
“…However, most publications seem to agree on the general anxiolytic status of morphine. In fact, morphine has already been shown to decrease fear-and anxiety-related behaviors in rhesus monkeys [59] and in humans [60]. Furthermore, injection of morphine in healthy rats either has no effect [26] or induces anxiolytic effects [61,62] when tested in the EPM.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, opioids have been used to treat psychological distress (mania and melancholia), as well as physical pain, 32,33 and more recently studies have suggested using opioids for treatment-resistant depression and anxiety. [34][35][36][37] It is also possible that depressed patients may experience their pain as more severe, which may prompt misuse. 38 A recent study of elderly adults supports the association of current depressive symptoms and opioid misuse.…”
Section: Discussion Opioid Misuse and Depressionmentioning
confidence: 99%
“…Despite this comorbidity there is evidence that such patients do well in opioid treatment and certainly no worse than non-depressed patients (Ngo et al, 2011;) (III). Higher doses may be needed for methadone-maintained patients with depression, and enrolment and stabilisation in such programmes alone is likely to have a beneficial effect on their psychiatric symptoms (Tenore, 2008) (IV). This may be a direct effect of opioid agonism on the reward pathway as well as secondary consequences on their chaotic lifestyle.…”
Section: Depressionmentioning
confidence: 99%